Preventing the spread of COVID-19 through environmental design in Thai community hospitals - Waroonkun, Tanut; Prugsiganont, Supuck (Frontiers in Built Environment, 2022)
The unprecedented outbreak of COVID-19 has had a tremendous negative impact on healthcare facilities, especially public hospitals. Thai community hospitals serve as primary care for COVID-19 patients. However, many hospital buildings were built during the 90s, and are now becoming outdated. This study aimed to identify the difficulties faced by the community hospitals by focusing on the physical settings of out-patient departments (OPD) during the Thailand COVID-19 outbreak between 2020 and 2021. Furthermore, the study focused on providing design suggestions for preventing the spread of respiratory infectious diseases. The study employed a three-step approach to data collection. The first was to observe the physical settings of the OPD of three hospital buildings. Secondly, interviews were conducted with thirty healthcare employees: 11 from the first hospital, 11 from the second hospital and 8 from the third hospital. Interviews were transcribed and analyzed using content analysis. Subsequently, the architectural design was produced based on observation and interview analysis. In the third step, the same thirty participants evaluated the architectural design through a focus group. Findings from the interviews led to four themes: (1) factors leading to the accumulation of pathogens, (2) measures for preventing the spread of respiratory diseases, (3) the effect of patient numbers on virus transmission, (4) suggestions for improving the physical setting of OPDs. The analysis of the four themes led to the preliminary design recommendation, which was evaluated through a focus group leading to suggestion for improvement of 13 areas. The analysis results showed that the participants were satisfied with the architectural design with additional minor recommendations. This study provided originality for the implementation and future development of hospital layout designs that can prevent the spread of COVID-19 throughout Thai community hospitals.